Barriers and Facilitators to the Use of Mental Health Services by Women With Elevated Symptoms of Depression and Their Partners. (1st September 2016) - Bell, Linda; Feeley, Nancy; Hayton, Barbara; Zelkowitz, Phyllis; Tait, Madeleine; Desindes, Sophie
Abstract : This qualitative descriptive study explored the barriers and facilitators to the use of mental health services reported by women with elevated symptoms of depression in the postpartum period and their partners. Data were collected through individual semi-structured interviews of 30 heterosexual couples. Content analysis revealed five principal barriers and facilitators: (a) accessibility and proximity, (b) appropriateness and fit, (d) stigma, (e) encouraged to seek help, and (f) personal characteristics. The study highlights the importance of barriers and facilitators to be taken into consideration in order to promote the use of mental health services for women with elevated symptoms of depression in the postpartum period.